Amino acids, proteins and exercise performance - Gibala, M. J.; Tipton, K.; Hargreaves, M. (2000)
In all but a few exceptional cases, the maximal contribution of protein as an energy source during exercise ranges between 2% and 10% of the total energy expended. In theory, amino acids could contribute to carbohydrate metabolism during exercise, but there is no hard evidence that this occurs or has any bearing on sport performance. Supplementation of the athlete's diet with branched-chain amino acids apparently does not benefit exercise performance. The most important factors for optimizing muscle growth when one trains with resistance exercise are making certain that the resistance is adequate, that the intake of dietary energy (calories) is sufficient, that at least a small amount of carbohydrate and/or protein is consumed immediately after each training session, and that the athlete obtains plenty of rest between training sessions. With rare exceptions, the maximal daily dietary protein requirements for athletes are in the range of 1.2-1.6 grams of protein per kilogram of body weight or about 3-4 ounces of protein per day for an athlete who weighs 160 pounds. This amount of protein can almost always be obtained in the normal diet. There is no solid evidence that special mixtures of amino acids provide any advantage over normal dietary proteins in stimulating muscle growth.